1987
DOI: 10.1136/adc.62.12.1220
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae meningitis in Sweden 1981-1983.

Abstract: SUMMARY Four hundred and seventy cases of meningitis caused by Haemophilus influenzae in children and 30 cases in adults were identified in Sweden between 1981 and 1983. The age specific incidence in the most susceptible age group (0-4 years) was 31/100 000/year (440 cases), which is higher than previously reported from Europe. A further 30 cases were seen in children aged 5-14. The risk of developing H influenzae meningitis before the age of 15 was 1 in 669. There were 11 deaths (2%) and five cases of serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 22 publications
5
16
1
1
Order By: Relevance
“…The country-wide epidemiological investigation on bacterial meningitis, upon which the present study is based, confirmed that the case-fatality rate and frequency of serious sequelae after bacterial meningitis in children in Sweden are relatively low in comparison with other industrialised countries [4,6,17,20,21,22,24,31,33]. The case-fatality rate was 3% and serious neurological sequelae were seen in 2% of all patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The country-wide epidemiological investigation on bacterial meningitis, upon which the present study is based, confirmed that the case-fatality rate and frequency of serious sequelae after bacterial meningitis in children in Sweden are relatively low in comparison with other industrialised countries [4,6,17,20,21,22,24,31,33]. The case-fatality rate was 3% and serious neurological sequelae were seen in 2% of all patients.…”
Section: Discussionsupporting
confidence: 83%
“…Bacterial meningitis, most often caused by Haemophilus influenzae type b (Hib), Neisseria meningitidis and Streptococcus pneumoniae, is a life threatening disease that causes death in 1%-15% of affected patients [3,33]. Survivors often have neurological sequelae and the reported rate of neurological sequelae varies between 10% and 50% [3].…”
Section: Introductionmentioning
confidence: 98%
“…With the virtual elimination of Hib in industrialized countries due to universal childhood vaccination programs, invasive Hi infection in adults has gained importance.A Swedish study estimated an annual incidence of 1.1 invasive infections per 100,000 adults [1]. Similar numbers were found in a US study with an overall annual incidence of 1.7 invasive infections per 100,000 adults [2].…”
Section: Introductionsupporting
confidence: 65%
“…Our case definition which includes only culture positive cases is similar to that of other international studies [3,4,9,15]. The inclusion by some researchers [5,7,8,12] of a small proportion of additional cases (on average less than one percent) that are Hib antigen positive but culture negative should not affect comparability of data.…”
Section: Discussionmentioning
confidence: 70%
“…Meningitis is the principal clinical disease [1,3,7] but other conditions such as epiglottitis, pneumonia, cellulitis, bone and joint infections and septicaemia also occur [4][5][6]. The major disease burden occurs in children under 5 years [3][4][5][6]8].…”
Section: Introductionmentioning
confidence: 99%